Utility of a super-flexible three-dimensional printed heart model in congenital heart surgery. (28th May 2018) - Hoashi, Takaya; Ichikawa, Hajime; Nakata, Tomohiro; Shimada, Masatoshi; Ozawa, Hideto; Higashida, Akihiko; Kurosaki, Kenichi; Kanzaki, Suzu; Shiraishi, Isao
Abstract: OBJECTIVES: The objective of this study was to assess the utility of 3D printed heart models of congenital heart disease for preoperative surgical simulation. METHODS: Twenty patient-specific 3D models were created between March 2015 and August 2017. All operations were performed by a young consultant surgeon who had no prior experience with complex biventricular repair. All 15 patients with balanced ventricles had outflow tract malformations (double-outlet right ventricle in 7 patients, congenitally corrected transposition of great arteries in 5, transposition of great arteries in 1, interrupted aortic arch Type B in 1, tetralogy of Fallot with pulmonary atresia and major aortopulmonary collateral arteries in 1). One patient had hypoplastic left heart complex, and the remaining 4 patients had a functional single ventricle. The median age at operation was 1.4 (range 0.1–5.9) years. Based on a multislice computed tomography data set, the 3D models were made of polyurethane resins using stereolithography as the printing technology and vacuum casting as the manufacturing method. RESULTS: All but 4 patients with a functional single ventricle underwent complete biventricular repair. The median cardiopulmonary bypass time and aortic cross-clamp time were 345 (110–570) min and 114 (35–293) min, respectively. During the median follow-up period of 1.3 (0.1–2.5) years, no mortality was observed. None of the patients experienced surgical heart block or systemic ventricular outflow tract obstruction. CONCLUSIONS: Three-dimensional printed heart models showed potential utility, especially in understanding the relationship between intraventricular communications and great vessels, as well as in simulation for creating intracardiac pathways.